2005
DOI: 10.2307/20031831
|View full text |Cite
|
Sign up to set email alerts
|

The Monetary Geography of Africa

Abstract: We would especially like to acknowledge our debt to our close collaborators. Xavier Debrun has coauthored with us several papers on monetary unions in Africa, and our book builds on that work. Heather Milkiewicz put together much of the data used in this book, has mastered the technology of creating maps, and has done much of the statistical analysis. Finally, Masson 9/23/03 List of Abbreviations and Acronyms AEC-African Economic Community, created by the 1991 Abuja Treaty AMU-Arab Maghreb Union, a regional gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 47 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, departing from the perspective of trade integration, there is yet no consensus in the literature on the monetary feasibility and advantages of monetary integration (Asongu & Diop, 2023). According to the corresponding literature (Asongu et al, 2017; Coulibaly & Gnimassoun, 2013; Masson & Pattillo, 2004), the plausibility of most of the potential monetary unions is yet to be established, namely the African Monetary Union (AMU), West African Monetary Zone (WAMZ), East African Monetary Union (EAMU) and Southern African Monetary Union (SAMU). The underlying perspective is supported in a comprehensive literature review by Asongu et al (2017) and recently confirmed by Asongu and Diop (2023), who have proposed an Index of African Monetary Integration (IAMI) in the light of apparent shortcomings from the extant literature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, departing from the perspective of trade integration, there is yet no consensus in the literature on the monetary feasibility and advantages of monetary integration (Asongu & Diop, 2023). According to the corresponding literature (Asongu et al, 2017; Coulibaly & Gnimassoun, 2013; Masson & Pattillo, 2004), the plausibility of most of the potential monetary unions is yet to be established, namely the African Monetary Union (AMU), West African Monetary Zone (WAMZ), East African Monetary Union (EAMU) and Southern African Monetary Union (SAMU). The underlying perspective is supported in a comprehensive literature review by Asongu et al (2017) and recently confirmed by Asongu and Diop (2023), who have proposed an Index of African Monetary Integration (IAMI) in the light of apparent shortcomings from the extant literature.…”
Section: Introductionmentioning
confidence: 99%